2014
DOI: 10.5194/nhess-14-2883-2014
|View full text |Cite
|
Sign up to set email alerts
|

Wind waves in the Black Sea: results of a hindcast study

Abstract: Abstract. In this study we describe the wind wave fields in the Black Sea. The general aims of the work were the estimation of statistical wave parameters and the assessment of interannual and seasonal wave parameter variability. The domain of this study was the entire Black Sea. Wave parameters were calculated by means of the SWAN wave model on a 5 × 5 km rectangular grid. Initial conditions (wind speed and direction) for the period between 1949 and 2010 were derived from the NCEP/NCAR reanalysis. According t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 47 publications
2
32
0
2
Order By: Relevance
“…The Black Sea is a semi-enclosed basin defined by an area of 423,000 km 2 2000 m. On a large scale, the wind conditions are under the influence of the Siberian and Azores high-pressure areas and by the Asian low-pressure area. It is expected that during the wintertime, the prevailing wind speeds (predominant values) are around 8 m/s (from northeast), while during the summer time we may expect wind conditions of 2-5 m/s coming from the northwest [28]. In addition, it is important to mention the local winds such as the breezes, which can account for 190 days/year in the southern part of Crimea, while this event is less noticeable in the western part of the sea.…”
Section: The Target Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The Black Sea is a semi-enclosed basin defined by an area of 423,000 km 2 2000 m. On a large scale, the wind conditions are under the influence of the Siberian and Azores high-pressure areas and by the Asian low-pressure area. It is expected that during the wintertime, the prevailing wind speeds (predominant values) are around 8 m/s (from northeast), while during the summer time we may expect wind conditions of 2-5 m/s coming from the northwest [28]. In addition, it is important to mention the local winds such as the breezes, which can account for 190 days/year in the southern part of Crimea, while this event is less noticeable in the western part of the sea.…”
Section: The Target Areamentioning
confidence: 99%
“…Energies 2018, 11, x FOR PEER REVIEW 3 of 17 prevailing wind speeds (predominant values) are around 8 m/s (from northeast), while during the summer time we may expect wind conditions of 2-5 m/s coming from the northwest [28]. In addition, it is important to mention the local winds such as the breezes, which can account for 190 days/year in the southern part of Crimea, while this event is less noticeable in the western part of the sea.…”
Section: The Target Areamentioning
confidence: 99%
“…SWAN accounts for wave propagation and transitions from deep to shallow water at finite depths by solving the spectral wave action balance equation, which includes source terms for the wind input, non-linear interactions, whitecapping, bottom friction and depth-induced breaking. The model performance, the parameterizations of the wave generation and dissipation processes and other aspects of SWAN applied to the Black Sea basin have been addressed in previous studies (Akpinar et al, 2012;Arkhipkin et al, 2014;Rusu et al, 2014). The model domain that is used for the simulations of our historical Black Sea storms is based on a numerical grid covering the entire Black Sea area (40-47 • N and 27-42 • E; hereafter named BUL; Fig.…”
Section: Wave Modelsmentioning
confidence: 99%
“…The operational surge model of Météo-France (Daniel et al, 2001) is a barotropic two-dimensional version of the HYbrid Coordinate Ocean Model (HYCOM) implemented by SHOM (Service Hydrographique et Océanographique de la Marine) from the three-dimensional version (Table 3; Bleck, 2002;Baraille and Filatoff, 1995 (Cancet et al, 2010). The bottom friction coefficient is spatially variable and has been optimized to properly reproduce the propagation of tides.…”
Section: Storm Surge Modelsmentioning
confidence: 99%
“…During the recent decades much efforts were made to improve our understanding of wind waves and corresponding processes in the Black Sea. Wave climate studies corresponding to the entire Black Sea can be found in, e. g., [1], [2]. Another important study subject are storms and their longterm variability [3; 4] as well as waves related to them [5].…”
Section: Introductionmentioning
confidence: 99%